Langerhans cells infiltration in lymph nodes of patients with systemic lupus erythematosus - Lei Li; Chengde Yang; Yue Yang; Jialin Teng; Hui Shi; Yuying Fan; Jing Lv; Haoyu Pan; Jinyi Qian; Yingjie Jiang; Qianchen Ma; Xiaohan Wei; et al. (Lupus Science and Medicine)
Objective This study aimed to characterise the clinical features and treatment regimens of patients with lupus who have lymphadenopathy (LAP), as well as to investigate the presence and potential implications of Langerhans cells (LCs) infiltration in lymph nodes.Methods A case-control study was conducted to identify the clinical characteristics of newly diagnosed, treatment-naïve patients with lupus who have LAP. Lymph node biopsies were performed, and LC infiltration was assessed using immunohistochemical staining for S100, CD1a and Langerin.Results A total of 59 patients with SLE who have LAP (SLE-LAP) were enrolled, with 81 patients with SLE without LAP serving as controls. The SLE-LAP group exhibited significantly higher frequencies of fever (64.4% vs 35.8%, p<0.001), anaemia (71.2% vs 42.0%, p<0.001), serous effusion (27.1% vs 11.1%, p=0.015), myositis (10.2% vs 1.2%, p=0.045) and elevated CRP levels (44.1% vs 22.2%, p=0.006). Moreover, autoantibodies, including anti-Smith (37.3% vs 16.0%, p=0.004), anticardiolipin IgG (27.1% vs 11.1%, p=0.015), IgM (42.4% vs 9.9%, p<0.001) and IgA (8.5% vs 0.0%, p=0.027), were more frequently detected in the LAP group. LC infiltration was confirmed in 29 of the 59 lymph node biopsies (49.2%). Immunohistochemical analysis revealed a scattered (58.6%) or focal (41.4%) distribution of LCs. Patients with LC infiltration predominantly presented with fever (72.4%), anaemia (64.3%), skin rashes (62.1%) and arthritis (62.1%). However, no significant differences in clinical manifestations were observed between LC-positive and LC-negative patients.Conclusion LC infiltration in the lymph nodes of patients with SLE is relatively common and should be carefully evaluated to prevent misdiagnosis. The role of LCs in the autoimmune response and pathogenesis of SLE warrants further investigation.